DEVELOPMENT OF 4K SKILLS IN PRIMARY EDUCATION WITH A MULTIDISCIPLINARY APPROACH (EXAMPLE OF STEAM) - Niyazmetova Zuxra (Bright Mind Publishing, 2026)
This article examines the development of 4C skills critical thinking, creativity, collaboration and communication through a multidisciplinary STEAM (Science, Technology, Engineering, Arts, Mathematics) approach in primary education. The article analyzes how STEAM-based lessons and projects affect the formation of students' 4C skills. The results show that a multidisciplinary approach increases students' creative thinking and problem-solving skills, as well as their teamwork and communication skills. This study highlights the importance of multidisciplinary and STEAM approaches in building 21st-century skills.
Keywords: Elementary Education, 4C Skills, STEAM Education, Multidisciplinary Approach, Creativity, Critical Thinking, Collaboration, Communication.